For the Sake of Family and Tradition: Honour Killings in India and Pakistan. Issue 1 (June 2020) - D'Lima, Tanya; Solotaroff, Jennifer L.; Pande, Rohini Prabha
The United Nations Population Fund (UNFPA) estimates that the annual worldwide number of honour killings is as high as 5, 000 women and girls, though some non-governmental organizations (NGOs) estimate as many as 20, 000 honour killings annually worldwide. Despite limited statistics, research shows that honour killings occur amongst women of different ages, religions, and social status, wealth, education, and location. The limited understanding of each country context, combined with scarce data on honour killings, has contributed to the continued hidden nature of this shocking form of violence. In this article, we seek to address this gap through a descriptive analysis of honour killings in India and Pakistan. In the absence of other data, we conduct a content analysis of media-reported honour killings in these two countries to examine key similarities and differences in the motivations, types, and other characteristics of honour killings across these countries and highlight any key risk and protective factors that emerge.